Visible light flashes induced by pulsed stimulated Brillouin scattering in narrow-linewidth, high-power, near-IR fiber lasers. (4th June 2021) - Choudhury, Vishal; Aparanji, Santosh; Prakash, Roopa; Balaswamy, V; Supradeepa, V R
Abstract: We report an interesting observation of visible light flashes indicating pulsing events in Near Infrared fiber laser systems. Using a narrow-linewidth, continuous-wave (CW) fiber laser operating at 1064 nm, we observed visible flashes composed of faint, red, orange, yellow and green colors. Concurrently with the visible flashes, the spectra in the backward direction showed different Raman Stokes orders of 1064 nm for a silica medium. We attribute this form of visible light generation to Cherenkov-type phase-matched harmonic generation in optical fibers enabled by high-peak-power parasitic pulses. These pulses are attributed to the onset of stimulated Brillouin scattering. The harmonics of different Raman Stokes orders of the pulses are responsible for the different visible colors observed. This effect is potentially observable in any laser system with a high optical power with a CW, quasi-CW or pulsed form.